Guidelines for the management of diabetes in care homes during the Covid‐19 pandemic. Issue 7 (15th June 2020) - Sinclair, A.; Dhatariya, K.; Burr, O.; Nagi, D.; Higgins, K.; Hopkins, D.; Patel, M.; Kar, P.; Gooday, C.; Howarth, D.; Abdelhafiz, A.; Newland‐Jones, P.; et al.
Abstract: The National Diabetes Stakeholders Covid‐19 Response Group was formed in early April 2020 as a rapid action by the Joint British Diabetes Societies for Inpatient Care, Diabetes UK, the Association of British Clinical Diabetologists, and Diabetes Frail to address and support the special needs of residents with diabetes in UK care homes during Covid‐19. It was obvious that the care home sector was becoming a second wave of Covid‐19 infection and that those with diabetes residing in care homes were at increased risk not only of susceptibility to infection but also to poorer outcomes. Its key purposes included minimising the morbidity and mortality associated with Covid‐19 and assisting care staff to identify those residents with diabetes at highest risk of Covid‐19 infection. The guidance was particularly created for care home managers, other care home staff, and specialist and non‐specialist community nursing teams. The guidance covers the management of hyperglycaemia by discussion of various clinical scenarios that could arise, the management of hypoglycaemia, foot care and end of life care. In addition, it outlines the conditions where hospital admission is required. The guidance should be regarded as interim and will be updated as further medical and scientific evidence becomes available. Novelty statement: This rapid response guidance represents the first national stakeholder action to address the special needs and vulnerabilities of care home residents with diabetes during Covid‐19 This guidance is designed to support clinical decision‐making in care homes and takes into account the availability of skilled personnel and level of care present, and the inevitable limitations on diabetes monitoring A set of different clinical scenarios are given covering the various likely situations care staff will face with residents with diabetes who develop Covid‐19 and what are the key actions to take to improve outcomes The guidance provides an optimal level of diabetes care approach during the exceptional circumstances of this pandemic but the Response Group recognises that care home settings may not be able to fully meet this unprecedented challenge